Epidemiological Survey of Human Dermatophytosis due to Zoophilic Species in Tehran, Iran - Babak HASSANZADEH RAD; Seyed Jamal HASHEMI; Maryam FARASATINASAB; Javaneh ATIGHI (Tehran University of Medical Sciences, 2018)
Background: Dermatophytosis is known as one of the most frequent cutaneous infections that lead to public health problems to human and animals. The purpose of this study was to determine the prevalence of human dermatophytosis due to zoophilic species in Tehran, Iran from 2014 to 2015.  Methods: Overall, 3989 patients with clinically suspected fungal infections were studied. Samples of skin, hair, and nails were examined by direct examination and culture. Direct microscopic examination was performed by KOH 15% for skin, KOH and DMSO for nail clippings and lactophenol for hair. Specimens were cultured on Sabouraud dextrose agar and mycobiotic agar. Results: Of 3989 patients, 755 (19%) suffered from dermatophytosis. Out of isolated dermatophytes, 716 (94.8%) anthropophilic, 35 (4.6%) zoophilic and 4 (0.5%) were geophilic species. Among of 35 patients with zoophilic dermatophyte infections, 65.7% were female. The most common type of zoophilic dermatophytosis according to anatomical areas was tinea manuum (34.3%) followed by tinea faciei (22.9%), tinea pedis (20%). Trichophyton verrucosum (57.1%) was the most commonly causative agents of zoophilic dermatophyte infections followed by Microsporum canis (42.9%). Conclusion: Our study showed epidemiological trends in the etiology of the agents causing dermatophytosis have changed in Tehran. Although the prevalence of zoophilic species declined in recent years, due to the tendency of most people to change lifestyles and increased urbanization, promotion of public health care and identification of new preventive and therapeutic strategies are necessary.